Manipulation of Growth and Architectural Characteristics in Trees for Increased Woody Biomass Production - Busov, Victor B. (Frontiers in Plant Science, 2018)
Growth and architectural traits in trees are economically and environmentally important and thus of considerable importance to the improvement of forest and fruit trees. These traits are complex and result from the operation of a number of molecular mechanisms. This review will focus on the regulation of crown architecture, secondary woody growth and adventitious rooting. These traits and processes have significant impact on deployment, management and productivity of tree crops. The majority of the described work comes from experiments in model plants, poplar, apple, peach and plum because these species allow functional analysis of the involved genes and have significant genomics resources. However, these studies convincingly show conserved mechanisms for elaboration of specific growth and architectural traits. The conservation of these mechanisms suggest that they can be used as a blueprint for the improvement of these traits and processes in phylogenetically diverse tree crops. We will specifically consider the involvement of flowering time, transcription factors and hormone-associated genes. The review will also discuss the impact of recent technological advances as well as the challenges to the dissection of these traits in trees.